Comparative analysis of complete plastid genome reveals powerful barcode regions for identifying wood of Dalbergia odorifera and D. tonkinensis (Leguminosae). Issue 1 (9th June 2020) - Qin, Ming; Zhu, Cheng‐Jie; Yang, Jun‐Bo; Vatanparast, Mohammad; Schley, Rowan; Lai, Qiang; Zhang, Dan‐Yan; Tu, Tie‐Yao; Klitgård, Bente B.; Li, Shi‐Jin; Zhang, Dian‐Xiang
Abstract: Dalbergia odorifera T. C. Chen (Leguminosae), a rare and endangered tree species endemic to Hainan Island of China, produces the most expensive and rarest wood in China. The wood characteristics of D. odorifera are remarkably similar to those of D. tonkinensis (a much less sought‐after species from Vietnam), and the DNA from wood is often highly degraded, making it very difficult to identify the two species using anatomical features or DNA barcoding based on regular DNA markers. To solve the confusion of identifying wood reliably from the two species, we built and analyzed the plastome library of 26 samples from 18 Dalbergia species, of which 12 samples from eight closely related species of D. odorifera are newly sequenced in this study. Phylogenomic analysis suggested that the relationships among the 26 samples are mostly well resolved, and conspecific individuals from different populations of D. odorifera and D. tonkinensis clustered together. Between the plastid genomes of the two species, we identified 129 indels and 114 single nucleotide polymorphisms. By assessing a subset of 20 nucleotide polymorphisms and 10 indels using 37 population‐level samples (20 samples of D. odorifera and 17 samples of D. tonkinensis ), we recovered eight species‐specific barcode regions that could be suitable for identifying the wood D. odorifera and D. tonkinensis . To examine their utility in wood identification, we amplified the eight DNA barcodes using six wood samples and recovered an amplification success rate of 83.3%, demonstrating a reliable method for precise wood identification of the two species.